2004
DOI: 10.1111/j.1749-7345.2004.tb00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Carp Hypophthalmichthys molitrix and Freshwater Mussel Elliptio complanata Filtration on the Phytoplankton Community of Partitioned Aquaculture System Units

Abstract: Growers produce over 2.8 million kg of catfish (over $350 million wholesale revenue) annually in the United States. The microbiology of the phytoplankton community in culture water affects the growth and flavor of the catfish and is a consideration for growers. Filter feeders, like silver carp and freshwater mussels, in controlled growth systems are used to adjust the phytoplankton species. Our goal was to successfully control the algal populations with filter feeders in catfish production. We used silver carp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
7
15
0
Order By: Relevance
“…The ammonia level was higher in the control group than in the treatment groups containing mussels, but this difference was not significant (Table 1). Similar results were obtained in previous studies where lower concentrations of ammonia were recorded in ponds containing the mussel E. complanata (Mueller and et al, 2004) and the oyster C. gigas (Miranda et al, 2010), but no significant differences were observed between the treatment and control groups. McKenzie and Özbay (2010) also obtained results similar to ours but reported that ammonia levels occasionally increased significantly in the ponds containing mussels.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The ammonia level was higher in the control group than in the treatment groups containing mussels, but this difference was not significant (Table 1). Similar results were obtained in previous studies where lower concentrations of ammonia were recorded in ponds containing the mussel E. complanata (Mueller and et al, 2004) and the oyster C. gigas (Miranda et al, 2010), but no significant differences were observed between the treatment and control groups. McKenzie and Özbay (2010) also obtained results similar to ours but reported that ammonia levels occasionally increased significantly in the ponds containing mussels.…”
Section: Discussionsupporting
confidence: 91%
“…This supports the previous findings of Mueller et al, (2004) and Miranda et al, (2010). In contrast, McKenzie and Özbay (2010) recorded much higher concentrations of both nitrate and phosphate in the groups containing mussels than in the control group, although these differences were 99±1.00 Average mussel growth (mm) = Final lenght x width -Initial lenght x width Average mussel growth (g) = Final wet weight -Initial wet weight also not significant.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations